(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Introduction: By putting students in situations where they must actively solve problems, educational simulation is a teaching method that assesses participants’ knowledge and ability levels. The guidelines are established by the instructor to ensure a secure setting for experiential learning